An insertion mutation of the MECP2 gene in severe neonatal encephalopathy and ocular and oropharyngeal dyskinesia: a case report - Jianmin Liang; Cuijuan Xin; Meiying Xin; Guangliang Wang; Xuemei Wu (BMC, 2023)
Abstract Background Pathogenic variation of the MECP2 gene presents mostly as Rett syndrome in females and is extremely rare in males. Most male patients with MECP2 gene mutation show MECP2 duplication syndrome. Case presentation Here we report a rare case in a 10-month-old boy with a hemizygous insertion mutation in MECP2 as NM_001110792, c.799_c.800insAGGAAGC, which results in a frameshift mutation (p.R267fs*6). The patient presented with severe encephalopathy in the neonatal period, accompanied by severe development backwardness, hypotonia, and ocular and oropharyngeal dyskinesia. This is the first report of this mutation, which highlights the phenotype variability associated with MECP2 variants. Conclusions This case helps to expand the clinical spectrum associated with MECP2 variants. Close attention should be paid to the growth and development of patients carrying a MECP2 variant or Xq28 duplication. Early interventions may help improve symptoms to some certain extent.